METHODS OF TEACHING COMPUTER SCIENCE AT THE UNIVERSITY - Kypshakbayeva Aigerim,; Bissenbayeva Zhanat,; Tukhmarova Shyrynkul, (Scientific Journal of Pedagogy and Economics, 2021)
This article discusses the definition of teaching methods as a science, its object and subject, and features. The main components of the connection between the methodology of teaching computer science as a science and the main concepts of the educational process are also identified. The main focus is on generalizing the experience of teaching the discipline "Informatics" to students of humanitarian universities and highlighting interdisciplinary connections. The purpose of the article is to describe the intermediate results obtained during the study of the effective use of information technologies in the course of teaching students of a humanitarian university in the discipline "Informatics". The structure of the e-course in the self-study support system is presented. The place of the discipline "Informatics" in the training programs of students of the 1st year of the bachelor's degree in the areas of "Economics" is highlighted, the types of tasks for independent work of students are described, and an example of the design of educational materials for the case in the discipline "Informatics" is given. The main directions of improving the methodology of teaching the discipline "Informatics" are also outlined.